2022
DOI: 10.1111/pce.14298
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid‐induced cytoplasmic translocation of constitutive photomorphogenic 1 enhances reactive oxygen species accumulation through the HY5‐ABI5 pathway to modulate seed germination

Abstract: Seed germination is a physiological process regulated by multiple factors. Abscisic acid (ABA) can inhibit seed germination to improve seedling survival under conditions of abiotic stress, and this process is often regulated by light signals. Constitutive photomorphogenic 1 (COP1) is an upstream core repressor of light signals and is involved in several ABA responses. Here, we demonstrate that COP1 is a negative regulator of the ABA-mediated inhibition of seed germination. Disruption of COP1 enhanced Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Recently Chen et al (2022) reported that ABA induces ROS which represses seed germination and induces osmotic stress. Thus, we observed ROS accumulation in all genotypes under normal conditions and ABA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Chen et al (2022) reported that ABA induces ROS which represses seed germination and induces osmotic stress. Thus, we observed ROS accumulation in all genotypes under normal conditions and ABA.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chen et al (2022) have reported that ROS generation by ABA causes inhibition of seed germination, which recommended that mutation in OsINH2 and OsINH3 may inhibit seed germination through ROS, thus we investigated ROS accumulation. ROS is a secondary messenger which mediates different responses in the cell being disrupted by various stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies also showed that COP1 participated in stress responses through its translocation ability. ABA treatment induced the cytoplasmic translocation of COP1 and enhanced reactive oxygen species accumulation during seed germination (Chen et al, 2022). However, under prolonged treatment in seedlings, ABA-induced the nuclear translocation of COP1 and promoted salt stress tolerance by destabilising golden2-like1 protein to supress chloroplast development (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ABA induces nuclear accumulation of COP1 in the dark, thus activating COP1-mediated ABD1 degradation and ABI5 protein accumulation ( Peng et al, 2022 ). In contrast, COP1 negatively regulates ABA-mediated seed germination inhibition, as the cop1 mutant shows hypersensitivity to ABA under both light and dark conditions ( Chen et al, 2022 ; Peng et al, 2022 ). Under light conditions, ABA promotes COP1 enrichment in the cytoplasm, leading to the accumulation of HY5 and ABI5 proteins in the nucleus and increased ROS levels in seeds ( Chen et al, 2022 ).…”
Section: Light Integrates Aba and Ga Signaling During Seed Germinationmentioning
confidence: 99%
“…In contrast, COP1 negatively regulates ABA-mediated seed germination inhibition, as the cop1 mutant shows hypersensitivity to ABA under both light and dark conditions ( Chen et al, 2022 ; Peng et al, 2022 ). Under light conditions, ABA promotes COP1 enrichment in the cytoplasm, leading to the accumulation of HY5 and ABI5 proteins in the nucleus and increased ROS levels in seeds ( Chen et al, 2022 ). But how COP1 regulates ABI5 during seed germination under dark is still unclear.…”
Section: Light Integrates Aba and Ga Signaling During Seed Germinationmentioning
confidence: 99%